2014
DOI: 10.1016/j.egypro.2014.11.1000
|View full text |Cite
|
Sign up to set email alerts
|

Performance Demonstration and Evaluation of the Synergetic Application of Thermochromic Window and Phase Change Material in Passive Buildings

Abstract: As two of the most popular energy efficient materials, vanadium dioxide (VO2) glazing and phase change material (PCM) were associated together for the first time. The synergetic application performance was demonstrated in a fullscale passive room and evaluated via Energy Saving Index (ESI). ESI, a novel and concise index, can be used to evaluate the passive application performance of materials or components from an energy standpoint and characterize the performance of a passive building material or component f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…PCM glasses typically enable the soft dispersion of natural light within spaces: In their solid state, PCMs allow around 28% of visible light to pass through, whereas in their liquid state, VLT rises to more than 40% [61]. Despite the existence of translucent PCMs [62], the effectiveness of these technologies in terms of transmitting high-quality light remains a drawback. Furthermore, PCMs still have limitations, including challenges associated with selecting the appropriate melting temperature, concerning about the 3 In a study [60], it was found that wall and indoor air temperature fluctuation is decreased by 2.7°C and 1.4°C, respectively, in a building that incorporates PCM; moreover, also energy demand was reduced by 57% during winter.…”
mentioning
confidence: 99%
“…PCM glasses typically enable the soft dispersion of natural light within spaces: In their solid state, PCMs allow around 28% of visible light to pass through, whereas in their liquid state, VLT rises to more than 40% [61]. Despite the existence of translucent PCMs [62], the effectiveness of these technologies in terms of transmitting high-quality light remains a drawback. Furthermore, PCMs still have limitations, including challenges associated with selecting the appropriate melting temperature, concerning about the 3 In a study [60], it was found that wall and indoor air temperature fluctuation is decreased by 2.7°C and 1.4°C, respectively, in a building that incorporates PCM; moreover, also energy demand was reduced by 57% during winter.…”
mentioning
confidence: 99%